HUBUNGAN ANTARA EKONOMI KERAKYATAN DENGAN PANCASILA SILA KE-4 - Arif Ramadhan; Awaludin Sinur Kholis; Anita Trisiana (RESEARCH FAIR UNISRI, 2020)
Turn of thought and is spend some time talking about the economic system force of the people s in disorder no matter how directly associated with muamalat ran into financial difficulties the most number of the 4th SILA. Have gone before you that “force of the people s that is presided over by skillful and godly wisdom discretion in representative after being suspended from the children of a deceased”. That means even all the house of representatives had to be involved in determining economic policy must be in accordance with mutual agreement or consensus . It is meant to reach for a ideals of society fair, honest, responsible, and prosperous. So that economic strength of the latest in a it is becoming concerned about more influenced a little bit about what an economic system that in practice the by to the state has solid . Indonesia when now applied economic system strategic i.e. the system economic kerakyatan, where in carrying out economic system controlled by the people. But in carrying out the economic system society-based have to need the considerations that were ripe , such as indonesia in determining sisem economic society-based. If you look at history, at the beginning of a developing country, especially Indonesia previously embraced the theory of growth in its economic system. Indonesia now does not adhere to the theory of growth because this principle actually experiences a failure. Therefore, Indonesia currently holds fast to the principle of populist economy.